2002
DOI: 10.1097/00007890-200202150-00024
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Chronic Plasmapheresis and Intravenous Heme-Albumin in Erythropoietic Protoporphyria After Orthotopic Liver Transplantation12

Abstract: Erythropoietic protoporphyria (EPP) is characterized by a deficiency of ferrochelatase the final enzyme of the heme biosynthetic pathway. Patients with EPP may overproduce protoporphyrin IX, chiefly in developing erythrocytes. In some, protoporphyrin accumulates and causes toxicity, particularly to the skin and liver. Orthotopic liver transplantation (OLT) treats the severe liver disease that sometimes occurs in EPP; however, it does not correct the underlying metabolic disorder. We recently reported a patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 8 publications
2
37
0
Order By: Relevance
“…The histology of his liver (Figure 2A) resembled that reported for allografts after orthotopic transplantation for EPP liver disease, where liver disease may recur within 9 months of exposure of a previously normal liver to excess protoporphyrin. 17,18 Our findings, together with previous reports of gross abnormalities of chromosome 18 in bone marrow in some patients with RARS or MDS and EPP, 7,9 show that an acquired somatic mutation of one FECH allele in hematopoietic cells is the usual explanation for the association of late-onset EPP with MPD and MDS, both conditions in which there is genetic instability. 19,20 Furthermore, management of this uncommon complication of MDS and MPD should include measures to prevent fatal protoporphyric liver disease.…”
Section: Resultssupporting
confidence: 77%
“…The histology of his liver (Figure 2A) resembled that reported for allografts after orthotopic transplantation for EPP liver disease, where liver disease may recur within 9 months of exposure of a previously normal liver to excess protoporphyrin. 17,18 Our findings, together with previous reports of gross abnormalities of chromosome 18 in bone marrow in some patients with RARS or MDS and EPP, 7,9 show that an acquired somatic mutation of one FECH allele in hematopoietic cells is the usual explanation for the association of late-onset EPP with MPD and MDS, both conditions in which there is genetic instability. 19,20 Furthermore, management of this uncommon complication of MDS and MPD should include measures to prevent fatal protoporphyric liver disease.…”
Section: Resultssupporting
confidence: 77%
“…The laboratory data at the time of transplant included an average total bilirubin of 13.2 mg/dl (range, 4.2-35), creatinine of 0.9 mg/dl (range, 0.5-2.6), and INR (measured or estimated from available prothrombin times) of 1.6 (range, 1.0-2.1). 33 The estimated MELD score in the patients prior to transplant was 21 (range, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…28 To treat EPP crisis and neuropathy, intravenous hematin therapy with or without plasmapheresis has been used. [29][30][31][32] The largest previous study, which reported the complications and outcomes of nine patients transplanted for EPP, was published in 1996 and showed that intermediate survival was good. 18 The present study includes those nine patients and adds eleven others who have been transplanted in the United States.…”
mentioning
confidence: 99%
“…These unsatisfactory outcomes for NLOD resulted from not only the growth retardation but also the fact that extrahepatic manifestations of these disorders disadvantageously affected the postoperative course of these patients. Recently, some therapeutic options for these extrahepatic manifestations of NLOD after LT have been reported to be efficacious (10,(20)(21)(22)(23). However, all of these reported therapies were symptomatic treatments and the evidence of their efficacy seemed to be anecdotal.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not each donor was a heterozygote for the recipient's disorder was determined by the mode of inheritance of each disorder (autosomal recessive inheritance for WD (3), TTI (9), GSD (10), PPA (4), MMA (4), CNSI (4) and BASD (11), autosomal dominant for EPP (12) and X-linked for OTCD (4)). In addition to our standard donor selection criteria, which have been described in detail elsewhere (13,14), some donors who were considered or suspected to be heterozygous carriers for their respective recipient's disorder underwent the following additional medical tests according to the disorder in question: for WD cases, assays for serum ceruloplasmin levels, urine copper excretion and the presence of Kayser-Fleischer corneal ring; for OTCD cases, quantitative serum amino acid analysis (QAAA) and allopurinol loading test (15,16); and for cases of PPA or MMA, serum propionic acid or methylmalonate level and the presence of metabolic acidosis confirmed by blood gas analysis.…”
Section: Methodsmentioning
confidence: 99%